Prevalence of Neuroradiological Abnormalities in First-Episode Psychosis - Muhammad Zulkarnain, Muhammad Zulkarnain; Aninda, Aninda (The Indonesian Journal of General Medicine, 2024)
Background: The exploration of neuroradiological abnormalities in first-episode psychosis has become increasingly significant, as highlighted by several studies that emphasize the importance of early detection and intervention. The literature consistently points to various structural brain abnormalities that may serve as biomarkers for understanding the onset and progression of psychotic disorders. Literature Review: This research supports a progressive neurodevelopmental model, indicating that structural changes not only precede the onset of psychosis but also worsen over time. This highlights the critical role of MRI as a potential biomarker for early intervention strategies. The role of MRI in schizophrenia, noting that while the neuropathology remains elusive, consistent structural and functional brain alterations are observed. The advancements in neuroimaging techniques allow for a more nuanced analysis of affected brain regions, enhancing the understanding of the disorder's complexity. Conclusion: In conclusion, the collective findings from these studies illustrate the prevalence and implications of neuroradiological abnormalities in first-episode psychosis. The evidence emphasizes the critical need for early neuroimaging in diagnosis and treatment, which may lead to a deeper understanding of the neurobiological underpinnings of psychotic disorders. The integration of neuroimaging with genetic and environmental studies holds promise for developing targeted interventions and improving outcomes for individuals experiencing their first episode of psychosis.